Implementation of discussion methods to increase indonesian language students’ achievement at the sixth grade students in sdn. 03 perawang barat in academic year 2014/2015 - Netti Yarni (Jurnal Ilmiah Pendidikan Scholastic, 2017)
In general, Indonesian lessons in the eyes of easy and considered trivial by students and even teachers themselves. This view has many implications for the less treatment of Indonesian subjects, making them less profitable for the development of the learning process and causing problems. This condition has an impact on the low student's daily test score, with an average of 55 so as not to achieve the completeness of learning (KKM) that has been implemented school 75. Therefore required a research action that aims to improve the learning process and improve learning outcomes by using Discussion methods. The formulation of the research are: "Whether the application of Discussion method can improve the learning outcomes of Indonesian students of Class VI SDN. 03 Perawang Barat in academic year 2014/2015?”. Subjek were students of class VI SDN. 03 PerawangBarat which amounted to 30 students. This action study was conducted in 2 cycles, each cycle consisting of 2 meetings. The research procedure consists of planning, execution, observation and reflection with research instrument in the form of learning device that is RPP, LKS, obsevation sheet of teacher and student. In the first cycle of student learning achievement reaches KKM as many as 19 students (63,27%). And on the second cycle student learning outcomes increased to 29 students (96.42%). From the results of this study can be concluded that the application of discussion methods can improve the learning outcomes of Indonesian students of Class VI SDN. 03 Perawang Barat in academic year 2014/2015.